The succession of international treaties in contemporary practice - Dimitrijević Duško (Međunarodni Problemi)
Succession of states is a process of substitution of state subjects concerning responsibility of international legal relations of the territory to which the succession relates to. No general rules and unwillingness of states to apply particular rules on succession often caused extreme difficulties in the past in analyzing the succession of treaty rights and obligations. As a totally incomplete system that would serve to regulate all problems caused by the change of the state territorial sovereignty in time the law of succession has manifested a tendency towards “adjustment” of customary rules to the factual situation. The contemporary examples of dissolution of the USSR, Czechoslovakia and SFR Yugoslavia, re-unification of Germany, as well gaining of independence by the Baltic States prove the assertion mentioned above. However, succession does not always prejudice legal substitution of states with regard to their rights and obligations. The study of the legal consequences of the process of succession of states presumes the application of a comparative method in the analysis of the state practice as well as the implementation of rules and principles of international law codificated in the 1978 Vienna Convention on Succession of States in Respect of Treaties.